Development and verification of kinematic wave analytical rainfall-runoff model - Teo, Alan Boon Hwee. (2009)
In this study, based on kinematic wave theory, a kinematic wave model has been developed for the flow on an overland plane and in channels of nine different shapes. The channel shapes are square, wide rectangular, deep rectangular, triangular, vertical curb, parabolic, circular, trapezoidal with equal side slope and trapezoidal with one side vertical. For verification, the model has been applied to three artificial and one natural catchment. The three artificial catchments consist of a concrete plane, asphalt plane and concrete catchment. The natural catchment is the Upper Bukit Timah catchment. The developed catchment model has been applied to the six events for the three artificial catchments and four events for the Upper Bukit Timah catchment. For the artificial catchments, the comparison of simulated and observed hydrographs shows that they are nearly perfect fit, and for the Upper Bukit Timah catchment, the comparison shows that they are very good fit. The kinematic wave model is therefore a reliable tool for simulating runoff hydrograph.